HUMAN PAPILLOMA VIRUS ASSOCIATED CERVICAL CANCER: A REVIEW - Kirti; Prabhakar, Pranav Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Globally, cervical cancer is the second most common cancer, and in India, it is the most common cancer in women. Human papilloma virus (HPV) is the main cause of it. Although there are several methods for preventing cervical cancer, primary prevention by vaccination is the most effective option. HPV vaccine is safe and effective. It is expensive and is not a replacement for periodic cervical screening procedures. In developing countries, the costeffectiveness of the vaccine and that of effective screening program with broader coverage is questionable. Today, HPV vaccine with regular cervical cancer screening program is the best possible tool to prevent cervical cancer. Keywords: Papilloma, Cervical, E6, E7, Cancer, Epithelium.